Molecular cloning of viral DNA from human genital warts. - de Villiers, E M (1981)
The DNA of human papilloma virus type 6 (HPV 6) has been cloned in Escherichia coli K-12 by using pBR322 as vector. The DNA was cloned at the BamHI and EcoRI cleavage sites. This DNA was mapped by employing further restriction endonucleases and by terminal labeling. No major differences were noted as compared to HPV 6 DNA originating directly from a genital wart. The existence of at least two DNA subtypes (HPV 6a and 6b) became apparent.